Impact of Coronavirus-19 Pandemic and Lockdown on Admissions for Ischemic Heart Disease - Puche, Juan E.; Iturregui-Guevara, Marta; Silva, Etelvino; Campuzano, Raquel; Vázquez., Rafael (Cardiology and Cardiovascular Medicine, 2022)
Background: In early 2020, the SARS-CoV-2 pandemic caused an unprecedented overload for the health service. A decrease in admissions for Acute Coronary Syndrome (ACS) was reported during lockdown, although many aspects remain to be clarified. The main objective of this study was to evaluate the impact of the pandemic and of lockdown itself in this area. Methods: We performed a retrospective observational study based on data from patients who visited the emergency department of a tertiary hospital with chest pain during 2018-2020, as well as those who were admitted for ACS. Personal details, date of admission, additional test results (laboratory and echocardiography), and therapy were recorded. Patients were divided into 3 groups: preCOVID (n=1,301), lockdown (n=45), and postlockdown (n=343). Results: Fewer visits to the emergency department for chest pain and admissions for ACS were recorded during lockdown (48.6% and 51.1% respectively, p<0.05). Patients who were admitted during lockdown were characterized by poorer control of cardiovascular risk factors, visited later (more evolving infarctions: 2.7% vs. 14.3%, p<0.05), experienced more echocardiographic complications during admission, and had more than 3-fold mortality rates (both in-hospital and postdischarge). Conclusion: The COVID-19 pandemic and lockdown itself had a negative effect on ischemic heart disease beyond SARS-CoV-2 infection.